PENGARUH MISKONSEPSI SISWA TERHADAP HASIL BELAJAR FISIKA PADA KONSEP GAYA DAN APLIKASINYA DI SMPN 1 KUOK KABUPATEN KAMPAR - Miftahul Husna; Fakhruddin Z Fakhruddin Z; M. Nor M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract :This research aims to know the influence of students' misconceptions towards the physics learning outcomes on the force concept and its applications in SMP I Kuok Kabupaten Kampar. This research uses a quantitative approach with survey method. The subject of reasearch was 82 students selected randomly as samples from overall population of class VIII students. The instruments used in this research is the diagnostic test to indicate the level of students’ misconceptions. Besides researcher also done documentation of physics learning outcomes on the concept of the force and its application.The analysis used in this research is descriptive analysis and inferential analysis. From descriptive analysis informed that students’ misconceptions reached very high level while physics learning outcomes was at low level. Inferential analysis consist of correlation and regression analysis. Correlation analysis of both variables produced a coefficient correlation-0,260. It showed that correlation between students’ misconceptions and physics learning outcomes was low and not unidirectional. Regression analysis showed the contribution of students’ misconceptions toward physics learning outcomes by -0.480. Students’ misconceptions influence 6,8% of physics learning outcomes significantly. This result informed that students’ misconceptions influence physics learning outcomes on the force concept and its applications in SMP I Kuok Kabupaten Kampar negatively and significantly.Keyword : Students’ misconceptions, Physics Learning Outcomes, Force Concept and its Applications